2020
DOI: 10.1042/bsr20193979
|View full text |Cite
|
Sign up to set email alerts
|

Dietary vitamin A intake and the risk of ovarian cancer: a meta-analysis

Abstract: BACKGROUND: Previous studies have demonstrated some associations between dietary vitamin A intake and ovarian cancer risk with an inconsistent relationship. We therefore performed the present study to further explore the association between them. METHODS: Databases of PubMed, Embase, and Web of Science were retrieved up to September 1, 2019. Summarized relative risk (RR) with corresponding 95% confidence intervals (CI) were calculated. Stata 14.0 software was used for data analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
1
7
0
1
Order By: Relevance
“…Vitamin A activity is important for normal control of cellular differentiation and proliferation and hypothesized to modify cancer risk. Interestingly, a previous study exploring the correlation between vitamin A levels and risk of OC demonstrated no association while a subsequent meta-analysis reached the opposite conclusion (79,80). A further MR analysis using two SNPs on a Caucasian population showed no causal link between vitamin A levels and risk of OC (37).…”
Section: Vitamin Amentioning
confidence: 92%
“…Vitamin A activity is important for normal control of cellular differentiation and proliferation and hypothesized to modify cancer risk. Interestingly, a previous study exploring the correlation between vitamin A levels and risk of OC demonstrated no association while a subsequent meta-analysis reached the opposite conclusion (79,80). A further MR analysis using two SNPs on a Caucasian population showed no causal link between vitamin A levels and risk of OC (37).…”
Section: Vitamin Amentioning
confidence: 92%
“…Podem ainda não ser devidamente absorvidos se não houver estratégias de ingestão que favoreçam sua biodisponibilidade de absorção. Alguns suplementos podem interagir negativamente com alguns medicamentos, como exemplo, a ação da vitamina K na redução da ação anticoagulante da varfarina (derivado cumarínico que atua como antagonista da vitamina K, utilizado na profilaxia e tratamento de diversas doenças tromboembólicas e suas complicações) (Polito et al, 2019); suplementos com dose elevadas de vitaminas C e E podem reduzir a eficácia de algumas categorias de quimioterapia contra o câncer (Burns et al, 2013); o excesso de vitamina A pode causar cefaléia, danos hepáticos e reduzir a resistência óssea (Wang & He, 2020); o excesso de ferro pode causar náuseas e vômitos e danificar órgãos internos, como o fígado e competir com cálcio (Pietrangelo, 2016).…”
Section: Potenciais Infortúnios Dos Recursos Ergogênicos Nutricionaisunclassified
“…Chronopoulou et al, has reported that extraction of vit A from Tetradesmus Obliquus is in the highest amount through supercritical fluid extraction method (Chronopoulou et al, 2019). Higher intake of dietary Vit A can remarkably decrease the ovarian, lung, gastric, pancreatic, and cervical carcinoma risk (Sanusi, 2019;Wang and He, 2020). Retinoic acid activates the extracellular-signal-regulated kinase (ERK) pathway and thus, promotes angiogenesis and metastasis in lung cancer.…”
Section: Vitaminsmentioning
confidence: 99%
“…Higher intake of dietary Vit A can remarkably decrease the ovarian, lung, gastric, pancreatic, and cervical carcinoma risk ( Sanusi, 2019 ; Wang and He, 2020 ). Retinoic acid activates the extracellular-signal-regulated kinase (ERK) pathway and thus, promotes angiogenesis and metastasis in lung cancer.…”
Section: Potential Microalgal Antioxidants For Use In Cancer Therapiementioning
confidence: 99%